2009
DOI: 10.1890/08-1263.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal source–sink dynamics at the edge of a species' range

Abstract: The roles of dispersal and population dynamics in determining species' range boundaries recently have received theoretical attention but little empirical work. Here we provide data on survival, reproduction, and movement for a Virginia opossum (Didelphis virginiana) population at a local distributional edge in central Massachusetts (USA). Most juvenile females that apparently exploited anthropogenic resources survived their first winter, whereas those using adjacent natural resources died of starvation. In spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 25 publications
0
44
1
Order By: Relevance
“…Data on current habitat use and preferences, in conjunction with historical records and published information, support the assertion that the pre-settlement distribution of the Swift Fox was largely limited to the shortgrass and mixed-grass ecosystems. By definition, the Swift Fox should encounter the boundary of its realized niche at the edge of its range, where environmental conditions are less than ideal and habitat quality declines (sensu Kanda et al 2009). Grassland ecosystems, however, are inherently dynamic, and the edges of the historical range of the Swift Fox undoubtedly were pliant and reflected prevailing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data on current habitat use and preferences, in conjunction with historical records and published information, support the assertion that the pre-settlement distribution of the Swift Fox was largely limited to the shortgrass and mixed-grass ecosystems. By definition, the Swift Fox should encounter the boundary of its realized niche at the edge of its range, where environmental conditions are less than ideal and habitat quality declines (sensu Kanda et al 2009). Grassland ecosystems, however, are inherently dynamic, and the edges of the historical range of the Swift Fox undoubtedly were pliant and reflected prevailing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This overall pattern of buffering from extreme environmental conditions may explain why few urban wildlife studies have identified density-independent factors as important for limiting populations. One notable exception would be the heat island effect in large urban centers reducing the limiting effect of winter weather at northern latitudes for some species (e.g., opossums, Kanda et al 2009). Other possible density-independent factors may include roads and toxins, such as rodenticides (Chaps.…”
Section: Density-independent Factorsmentioning
confidence: 99%
“…Thus, adaptation is used in a restricted sense in this paper to mean a population that has evolved to have an absolute fitness greater than one in the habitat in which it exists. There are a growing number of examples of systems with source-sink structure (e.g., Breininger and Carter 2003;Breininger and Oddy 2004;Johnson 2004;Caudill 2005;Kanda et al 2009). …”
Section: Introductionmentioning
confidence: 99%